2012
DOI: 10.1371/journal.pone.0032667
|View full text |Cite
|
Sign up to set email alerts
|

Amplified Genes May Be Overexpressed, Unchanged, or Downregulated in Cervical Cancer Cell Lines

Abstract: Several copy number-altered regions (CNAs) have been identified in the genome of cervical cancer, notably, amplifications of 3q and 5p. However, the contribution of copy-number alterations to cervical carcinogenesis is unresolved because genome-wide there exists a lack of correlation between copy-number alterations and gene expression. In this study, we investigated whether CNAs in the cell lines CaLo, CaSki, HeLa, and SiHa were associated with changes in gene expression. On average, 19.2% of the cell-line gen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
44
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 50 publications
(48 citation statements)
references
References 53 publications
3
44
0
Order By: Relevance
“…It has been reported that the copy number of ECT2-located 3q26 frequently increases in several cancers including head and neck, lung and cervical cancer, suggesting that a genomic imbalance may contribute to the upregulation of ECT2 in OS (10,11). ECT2 has been considered to play an oncogenic role in several malignant tumors, including ovarian cancer, retinoblastoma, pancreatic ductal adenocarcinoma, cervical and colorectal cancers, oral squamous cell carcinoma, as well as OS (9,(12)(13)(14)(15)(16)(17). In the present study, it was shown that the expression of ECT2 was significantly upregulated in OS tissues when compared with that in normal adjacent tissues.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…It has been reported that the copy number of ECT2-located 3q26 frequently increases in several cancers including head and neck, lung and cervical cancer, suggesting that a genomic imbalance may contribute to the upregulation of ECT2 in OS (10,11). ECT2 has been considered to play an oncogenic role in several malignant tumors, including ovarian cancer, retinoblastoma, pancreatic ductal adenocarcinoma, cervical and colorectal cancers, oral squamous cell carcinoma, as well as OS (9,(12)(13)(14)(15)(16)(17). In the present study, it was shown that the expression of ECT2 was significantly upregulated in OS tissues when compared with that in normal adjacent tissues.…”
Section: Discussionmentioning
confidence: 99%
“…The role of ECT2 upregulation in other cancers has been widely demonstrated (9,(12)(13)(14)(15)(16)(17); however, these studies mainly focused on its effect on cell cycle progression. For instance, Iyoda et al observed that ECT2 was notably upregulated in oral squamous cell carcinoma, and that the inhibition of ECT2 caused cell cycle arrest at the G1 phase, accompanied by the upregulation of the cyclin-dependent kinase (CDK) interacting protein/kinase inhibitory protein family of CDK inhibitors, as well as downregulation of cyclin D1, cyclin E and CDK4 (17).…”
Section: Discussionmentioning
confidence: 99%
“…A CLPTM1L haplotype has been found to confer glioma risk (16). Chromosome 5p is commonly duplicated in cervical cancer cell lines, however, of the genes within the cancer associated 5p15.33 region, only CLPTM1L is overexpressed (19). Our previous studies demonstrated that CLPTM1L is overexpressed in lung adenocarcinoma (2).…”
Section: Introductionmentioning
confidence: 99%
“…Recent studies revealed that CLPTM1L expression was markedly increased in several types of tumor cell lines, including lung, cervical, and renal carcinoma lines [16,30,31]. CLPTM1L is also overexpressed in a number of different tumor tissues, such as lung cancer and laryngeal squamous cell carcinoma [15,32].…”
Section: Discussionmentioning
confidence: 99%